Nanocomposite amine liquid decarbonizing agent and preparation method thereof
By using a composite of nano-sized zirconium oxide and lithium oxide to improve the amine decarbonizing agent, the corrosion and stability problems of traditional amine decarbonizing agents have been solved, achieving more efficient carbon dioxide absorption and lower energy consumption, and showing broad prospects for industrial applications.
Patent Information
- Application Number
- CN202311046152.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-10-28
- Estimated Expiration
- 2043-08-18
AI Technical Summary
Traditional amine liquid decarbonizing agents have problems such as strong corrosivity, easy foaming, and easy degradation in industrial waste gas treatment, resulting in insufficient efficiency and stability.
A nanocomposite amine decarbonizing agent was prepared by combining nano-sized zirconium oxide and lithium oxide with amine liquid and through specific morphology and dispersibility treatment. The performance and stability of the agent were optimized by utilizing the synergistic effect of nano-sized zirconium oxide and lithium oxide.
It improves the corrosion resistance, foaming resistance and oxidation resistance of amine liquid decarbonizing agent, enhances decarbonization selectivity and absorption efficiency, reduces energy consumption and cost, and extends service life.
Abstract
Description
Technical Field
[0001] This article focuses on the fields of environmental protection and new materials. Specifically, it addresses the selectivity and stability issues of amine liquid decarbonizing agents used in industrial waste gas treatment. It utilizes the properties of nanocomposite materials to improve and optimize these agents, thereby enhancing their decarbonization selectivity and stability. Background Technology
[0002] Waste gas emissions are a significant environmental issue in industrial production processes. To reduce emissions of harmful gases such as carbon dioxide, amine liquid decarbonizing agents are widely used in industrial waste gas treatment. However, amine liquid decarbonizing agents themselves have some drawbacks, such as strong corrosiveness, easy foaming, and easy degradation, leading to problems with their efficiency and stability during use.
[0003] Nanocomposites are a novel type of material with great application potential. By combining nanoscale materials with other materials, materials with novel properties and functions can be created. Adding nanocomposites to amine decarbonizing agents can improve their performance and stability. For example, carbon nanotube / polymer composites can enhance the corrosion resistance, foaming resistance, and oxidation resistance of amine decarbonizing agents, improving their absorption and regeneration efficiency. Besides carbon nanotubes, other nanocomposites such as metal oxides, silicate clays, and graphene can also be added to amine decarbonizing agents. The amount, morphology, and distribution of these nanocomposites will have different effects on the performance and stability of amine decarbonizing agents, thus requiring specific optimization.
[0004] This invention provides a method for improving the decarbonization selectivity and stability of amine decarbonizing agents by adding nanocomposite materials. The innovation of this invention lies in using nanocomposite materials with specific morphology and dispersibility, which optimizes the physicochemical properties of the amine decarbonizing agent and improves its absorption and regeneration efficiency. The method provided by this invention can improve the decarbonization selectivity and stability of amine decarbonizing agents, thereby effectively reducing the emission of harmful gases such as carbon dioxide in industrial production. Summary of the Invention
[0005] This invention proposes a novel nanocomposite amine decarbonizing agent and its preparation method, which aim to improve the performance and stability of amine decarbonizing agents.
[0006] Compared to traditional amine decarbonizing agents, this decarbonizing agent has the following advantages: First, the addition of nanocomposite materials can significantly improve the corrosion resistance, oxidation resistance, and foaming resistance of the amine decarbonizing agent, thereby increasing its service life and stability. Second, this nanocomposite amine decarbonizing agent can improve decarbonization selectivity and absorption efficiency while reducing energy consumption and cost, thus improving decarbonization efficiency and economy. Furthermore, this decarbonizing agent also possesses the special properties of nanomaterials, such as large surface area, good dispersibility, and high reactivity, making it adaptable to the needs of different industrial scenarios and showing broad application prospects.
[0007] Based on the above characteristics and advantages, this novel nano-composite amine liquid decarbonizing agent can be widely used in waste gas treatment in industries such as steel, chemical, and power. Besides industrial applications, this decarbonizing agent can also be used in environmental protection and energy development, demonstrating broad application prospects and market value. Therefore, the development and application of this decarbonizing agent has significant social implications.
[0008] The main technical idea of this invention is to add nano-sized zirconium oxide and lithium oxide to amine solution to give it a specific morphology and dispersibility, thereby improving the performance and stability of amine solution decarbonizing agent.
[0009] This invention is implemented as follows:
[0010] The specific implementation method is as follows: A nano-composite amine liquid decarbonizing agent, characterized in that it comprises the following components:
[0011] a. Amines;
[0012] b. Nanoscale zirconium oxide with a particle size between 10 and 50 nm;
[0013] c. Nanoscale lithium oxide with a particle size between 10 and 50 nm;
[0014] d. Surfactants;
[0015] e. Auxiliary additives.
[0016] The amines include, but are not limited to, alkanolamines, etheramines, amides, and cyclic amines.
[0017] The surfactants include, but are not limited to, sodium dodecylbenzenesulfonate.
[0018] The auxiliary additives include, but are not limited to, sodium chloride, potassium chloride, etc.
[0019] The mass ratio of nano-sized zirconium oxide to lithium oxide is 1:2~3, and the amount of both added is 0.1~0.5 wt% of the total amount of decarbonizing agent.
[0020] The amount of surfactant added is 0.01~0.05 wt% of the total amount of decarbonizing agent.
[0021] The amount of the auxiliary additive is 0.1 to 0.5 wt% of the total amount of the decarbonizing agent.
[0022] The nano-composite amine liquid decarbonizing agent of the present invention has a viscosity of 20~100 mPa·s and a solubility of 20~35wt% in water.
[0023] This invention also provides a method for preparing a nano-composite amine liquid decarbonizing agent, which mainly includes the following steps:
[0024] a. Preparation of nanoscale zirconium oxide and lithium oxide: including the following steps:
[0025] i. Preparation of sol: Dissolve zirconium acetate and lithium acetate in a solvent to a concentration of 0.1~0.5 mol / L;
[0026] ii. Gelation: The sol prepared above is heated to 50~80℃ and gelation reaction is carried out under the condition of pH 3~6 for 12~14 hours;
[0027] iii. Drying and calcination: The gel prepared above is dried at 80~120℃ and then calcined at 500~950℃ for 13-15 hours;
[0028] iv. Post-processing: The calcined product is subjected to plasma treatment, ultrasonic treatment or heat treatment to obtain nano-sized zirconium oxide and lithium oxide;
[0029] b. Add the above-mentioned nano-sized zirconium oxide and lithium oxide to the amine solution, control their addition amount and dispersibility, and add surfactants and auxiliary additives at the same time, and continue to stir and mix to obtain nano-composite amine solution decarbonizing agent.
[0030] In this invention, the preparation of nano-sized zirconium oxide and lithium oxide is carried out by using a sol-gel method. During the preparation process, factors such as reaction temperature, time, and reactant concentration can be controlled, achieving high efficiency, controllability, and repeatability in the preparation of nano-sized zirconium oxide and lithium oxide. This ensures that the particle size and morphology of the prepared nano-sized zirconium oxide and lithium oxide meet the requirements, and that the properties and performance of the nano-sized zirconium oxide and lithium oxide reach their optimal state.
[0031] Preparation of the sol: The concentration of reactants is typically between 0.1 and 0.5 mol / L, and the type and ratio of solvent need to be selected according to the properties and requirements of the reactants. The solvent is one or a combination of acetone, ethanol, n-butanol, isopropanol, n-propanol, isobutanol, methanol, ethylene glycol, propylene glycol, dimethylformamide, ethyl acetate, benzene, and water. For example, zirconium acetate can be dissolved in solvents such as isopropanol, acetone, and n-propanol, while lithium acetate can be dissolved in solvents such as water and methanol. Taking zirconium acetate as an example, 0.2 mol / L zirconium acetate can be dissolved in acetone.
[0032] Gelation: The reaction temperature is generally between 50 and 80°C, the reaction time is about 12-14 hours, and the pH value is usually between 3 and 6. By controlling these parameters, the desired particle size and morphology can be obtained. Taking zirconium acetate as an example, it can be dissolved in acetone and heated to 60°C, and the gelation reaction can be carried out at a pH of 4 for 12-14 hours.
[0033] Drying and calcination: The drying temperature is generally between 80 and 120°C, and the time is about 12-14 hours, which can be adjusted according to the actual situation. The calcination temperature is generally between 500 and 950°C, and the time is about 13-15 hours. The atmosphere is usually air, nitrogen, hydrogen, etc. Taking zirconium acetate as an example, the gel can be dried at 80°C for 12-14 hours, and then calcined at 800°C under a nitrogen atmosphere and held for 4 hours.
[0034] Specifically, the nano-sized zirconium oxide and lithium oxide used in this invention have specific morphologies and dispersions, and their preparation method also includes specific post-processing techniques to ensure their stability and activity. These post-processing techniques include plasma treatment, ultrasonic treatment, and heat treatment, which further improve the activity and stability of the nano-sized zirconium oxide and lithium oxide, making them more suitable for addition to amine decarbonizing agents and optimizing their performance and stability. For example, plasma treatment can be one or more combinations of plasma-enhanced chemical vapor deposition, plasma-enhanced arc deposition, or plasma-enhanced thermoatomic deposition.
[0035] In this invention, the addition of nano-sized zirconium oxide and lithium oxide involves adding the prepared nano-sized zirconium oxide and lithium oxide to an amine solution, controlling the amount added and the dispersibility. In this invention, the mass ratio of nano-sized zirconium oxide to lithium oxide is 1:2~3, and the amount added is 0.1~0.5 wt%. Dispersibility can be controlled using methods such as mechanical stirring or ultrasonic dispersion. The frequency and time of ultrasonic dispersion can be adjusted according to specific needs, generally within the range of 20~40 kHz, for a time of 30~60 minutes. A surfactant (such as sodium dodecylbenzenesulfonate) is added to the amine solution. The resulting nano-composite amine solution decarbonizing agent can be stored at room temperature and exhibits long-term stability.
[0036] Through the above technical solutions, the nano-composite amine liquid decarbonizing agent of the present invention can improve the performance and stability of amine liquid decarbonizing agents, and enhance their corrosion resistance, foaming resistance, and oxidation resistance. Simultaneously, this decarbonizing agent can exhibit higher decarbonization selectivity and absorption efficiency, with a decarbonization efficiency exceeding 95%.
[0037] Compared with traditional amine decarbonizing agents, the nano-composite amine liquid decarbonizing agent involved in this invention has the following uniqueness and innovation:
[0038] (1) The particle size of nano-sized zirconium oxide and lithium oxide is controlled within the range of 10~50 nm. This is because small particles can increase surface area and reactivity, thereby improving selectivity and efficiency. Through appropriate surface treatment processes, the surface charge and hydrophilicity / hydrophobicity of nano-sized zirconium oxide and lithium oxide can be controlled, thereby optimizing their dispersibility and stability in amine solutions. The aggregation state of nano-sized zirconium oxide and lithium oxide can be controlled by using specific additives, thereby avoiding their agglomeration and precipitation, and improving the stability of the amine decarbonizing agent. Through appropriate stirring and ultrasonic treatment processes, the dispersibility and stability of nano-sized zirconium oxide and lithium oxide in amine solutions can be further improved, thereby improving their selectivity and decarbonization efficiency. The uniqueness and innovation of this invention lies in using nano-sized zirconium oxide and lithium oxide as additives in amine decarbonizing agents, and controlling their morphology and dispersibility through optimized post-treatment processes, thereby improving decarbonization efficiency and reducing costs.
[0039] (2) The synergistic effect of nano-sized zirconium oxide and lithium oxide is achieved through structure-activity relationship. Nano-sized zirconium oxide can act as a strong acidic site to adsorb and decompose CO2, while nano-sized lithium oxide can act as a weak basic site to adsorb and remove CO2. At the same time, nano-sized zirconium oxide can also adsorb and stabilize lithium oxide in amine solution, thereby increasing the available basicity and stability of amine solution and improving decarbonization efficiency and stability. Therefore, nano-sized zirconium oxide and lithium oxide can work synergistically to leverage their respective advantages and improve the performance and efficiency of amine solution decarbonization agent. After being added to amine solution, nano-sized zirconium oxide and lithium oxide can be adsorbed on the surface of amine solution molecules, increasing the available basicity and activity of amine solution, thereby increasing the rate and efficiency of decarbonization reaction. In addition, nano-sized zirconium oxide and lithium oxide can also increase the thermal stability and durability of amine solution, extending the service life of amine solution. By optimizing the addition amount and dispersibility of nano-sized zirconium oxide and lithium oxide, the performance and stability of amine solution decarbonization agent can be further improved, and the energy consumption and cost in the decarbonization process can be reduced. Therefore, the uniqueness and innovation of this invention lies in utilizing the synergistic effect of nano-sized zirconium oxide and lithium oxide to optimize the performance and stability of amine liquid decarbonizing agent and improve its application value in industrial decarbonization processes. Implementation
[0040] The present invention will now be described in detail with reference to embodiments, but is not limited to the contents described in the following embodiments. Example 1
[0041] a. Preparation of nanoscale zirconium oxide and lithium oxide: including the following steps:
[0042] i. Preparation of sol: Dissolve 0.5 mol / L zirconium acetate in a 1:1 mixture of methanol and ethanol, and dissolve 0.5 mol / L lithium acetate in methanol;
[0043] ii. Gelation: The sol prepared above was heated to 60°C and a gelation reaction was carried out at pH 4 for 12 hours;
[0044] iii. Drying and calcination: The gel prepared above was dried at 80°C and then calcined at 800°C for 13 hours, followed by a 4-hour holding time.
[0045] iv. Post-processing: The calcined product was subjected to plasma-enhanced chemical vapor deposition to obtain nano-sized zirconium oxide and lithium oxide;
[0046] b. Add the above-mentioned nano-sized zirconium oxide and lithium oxide to the amine solution, with a mass ratio of 1:2 and an addition amount of 0.1 wt%. Simultaneously, control the dispersibility by ultrasonic dispersion, with an ultrasonic frequency in the range of 30~35kHz and a time of 40~50 minutes. At the same time, add 0.05 wt% sodium dodecylbenzenesulfonate and 0.2 wt% sodium chloride, and continue stirring and mixing to obtain the nano-composite amine solution decarbonizing agent. Example 2
[0047] a. Preparation of nanoscale zirconium oxide and lithium oxide: including the following steps:
[0048] i. Preparation of sol: Dissolve 0.5 mol / L zirconium acetate in a 1:1 mixture of methanol and ethanol, and dissolve 0.5 mol / L lithium acetate in methanol;
[0049] ii. Gelation: The sol prepared above was heated to 60°C and a gelation reaction was carried out at pH 4 for 12 hours;
[0050] iii. Drying and calcination: The gel prepared above was dried at 80°C and then calcined at 800°C for 13 hours, followed by a 4-hour holding time.
[0051] iv. Post-processing: The calcined product was subjected to plasma-enhanced chemical vapor deposition to obtain nano-sized zirconium oxide and lithium oxide;
[0052] b. Add the above-mentioned nano-sized zirconium oxide and lithium oxide to the amine solution, with a mass ratio of nano-sized zirconium oxide to lithium oxide of 1:3 and an addition amount of 0.1 wt%. Simultaneously, control the dispersibility by ultrasonic dispersion, with an ultrasonic frequency in the range of 30~35kHz and a time of 40~50 minutes. At the same time, add 0.05 wt% sodium dodecylbenzenesulfonate and 0.2 wt% sodium chloride, and continue stirring and mixing to obtain the nano-composite amine solution decarbonizing agent. Example 3
[0053] a. Preparation of nanoscale zirconium oxide and lithium oxide: including the following steps:
[0054] i. Preparation of sol: Dissolve 0.5 mol / L zirconium acetate in a 1:1 mixture of methanol and ethanol, and dissolve 0.5 mol / L lithium acetate in methanol;
[0055] ii. Gelation: The sol prepared above was heated to 60°C and a gelation reaction was carried out at pH 4 for 12 hours;
[0056] iii. Drying and calcination: The gel prepared above was dried at 80°C and then calcined at 800°C for 13 hours, followed by a 4-hour holding time.
[0057] iv. Post-processing: The calcined product was subjected to plasma-enhanced chemical vapor deposition to obtain nano-sized zirconium oxide and lithium oxide;
[0058] b. Add the above-mentioned nano-sized zirconium oxide and lithium oxide to the amine solution, with a mass ratio of 1:2 and an addition amount of 0.3 wt%. Simultaneously, control the dispersibility by ultrasonic dispersion, with an ultrasonic frequency in the range of 30~35kHz and a time of 40~50 minutes. At the same time, add 0.05 wt% sodium dodecylbenzenesulfonate and 0.2 wt% sodium chloride, and continue stirring and mixing to obtain the nano-composite amine solution decarbonizing agent. Example 4
[0059] a. Preparation of nanoscale zirconium oxide and lithium oxide: including the following steps:
[0060] i. Preparation of sol: Dissolve 0.5 mol / L zirconium acetate in a 1:1 mixture of methanol and ethanol, and dissolve 0.5 mol / L lithium acetate in methanol;
[0061] ii. Gelation: The sol prepared above was heated to 60°C and a gelation reaction was carried out at pH 4 for 12 hours;
[0062] iii. Drying and calcination: The gel prepared above was dried at 80°C and then calcined at 800°C for 13 hours, followed by a 4-hour holding time.
[0063] iv. Post-processing: The calcined product was subjected to plasma-enhanced chemical vapor deposition to obtain nano-sized zirconium oxide and lithium oxide;
[0064] b. Add the above-mentioned nano-sized zirconium oxide and lithium oxide to the amine solution, with a mass ratio of nano-sized zirconium oxide to lithium oxide of 1:3 and an addition amount of 0.3 wt%. Simultaneously, control the dispersibility by ultrasonic dispersion, with an ultrasonic frequency in the range of 30~35kHz and a time of 40~50 minutes. At the same time, add 0.05 wt% sodium dodecylbenzenesulfonate and 0.2 wt% sodium chloride, and continue stirring and mixing to obtain the nano-composite amine solution decarbonizing agent. Example 5
[0065] a. Preparation of nanoscale zirconium oxide and lithium oxide: including the following steps:
[0066] i. Preparation of sol: Dissolve 0.5 mol / L zirconium acetate in a 1:1 mixture of methanol and ethanol, and dissolve 0.5 mol / L lithium acetate in methanol;
[0067] ii. Gelation: The sol prepared above was heated to 60°C and a gelation reaction was carried out at pH 4 for 12 hours;
[0068] iii. Drying and calcination: The gel prepared above was dried at 80°C and then calcined at 800°C for 13 hours, followed by a 4-hour holding time.
[0069] iv. Post-processing: The calcined product was subjected to plasma-enhanced chemical vapor deposition to obtain nano-sized zirconium oxide and lithium oxide;
[0070] b. Add the above-mentioned nano-sized zirconium oxide and lithium oxide to the amine solution, with a mass ratio of nano-sized zirconium oxide to lithium oxide of 1:2 and an addition amount of 0.5 wt%. Simultaneously, control the dispersibility by ultrasonic dispersion, with an ultrasonic frequency in the range of 30~35kHz and a time of 40~50 minutes. At the same time, add 0.05wt% sodium dodecylbenzenesulfonate and 0.2wt% sodium chloride, and continue stirring and mixing to obtain the nano-composite amine solution decarbonizing agent. Example 6
[0071] a. Preparation of nanoscale zirconium oxide and lithium oxide: including the following steps:
[0072] i. Preparation of sol: Dissolve 0.5 mol / L zirconium acetate in a 1:1 mixture of methanol and ethanol, and dissolve 0.5 mol / L lithium acetate in methanol;
[0073] ii. Gelation: The sol prepared above was heated to 60°C and a gelation reaction was carried out at pH 4 for 12 hours;
[0074] iii. Drying and calcination: The gel prepared above was dried at 80°C and then calcined at 800°C for 13 hours, followed by a 4-hour holding time.
[0075] iv. Post-processing: The calcined product was subjected to plasma-enhanced chemical vapor deposition to obtain nano-sized zirconium oxide and lithium oxide;
[0076] b. Add the above-mentioned nano-sized zirconium oxide and lithium oxide to the amine solution, with a mass ratio of nano-sized zirconium oxide to lithium oxide of 1:3 and an addition amount of 0.5 wt%. Simultaneously, control the dispersibility by ultrasonic dispersion, with an ultrasonic frequency in the range of 30~35kHz and a time of 40~50 minutes. At the same time, add 0.05wt% sodium dodecylbenzenesulfonate and 0.2wt% sodium chloride, and continue stirring and mixing to obtain the nano-composite amine solution decarbonizing agent.
[0077] Comparative Example 1
[0078] a. Preparation of nanoscale zirconium oxide and lithium oxide: including the following steps:
[0079] i. Preparation of sol: Dissolve 0.5 mol / L zirconium acetate in a 1:1 mixture of methanol and ethanol, and dissolve 0.5 mol / L lithium acetate in methanol;
[0080] ii. Gelation: The sol prepared above was heated to 60°C and a gelation reaction was carried out at pH 4 for 12 hours;
[0081] iii. Drying and calcination: The gel prepared above was dried at 80°C and then calcined at 800°C for 13 hours, followed by a 4-hour holding time.
[0082] iv. Post-processing: The calcined product was subjected to plasma-enhanced chemical vapor deposition to obtain nano-sized zirconium oxide and lithium oxide;
[0083] b. Add the above-mentioned nano-sized zirconium oxide and lithium oxide to the amine solution, with a mass ratio of nano-sized zirconium oxide to lithium oxide of 1:2 and an addition amount of 1 wt%. Simultaneously, control the dispersibility by ultrasonic dispersion, with an ultrasonic frequency in the range of 30~35kHz and a time of 40~50 minutes. At the same time, add 0.05wt% sodium dodecylbenzenesulfonate and 0.2wt% sodium chloride, and stir to mix to obtain a composite amine solution decarbonizing agent.
[0084] Comparative Example 2
[0085] Compared with Comparative Example 1, only nano-sized zirconium oxide was added, with an addition amount of 0.5 wt%.
[0086] Comparative Example 3
[0087] In a traditional amine solution, 0.05 wt% sodium dodecylbenzenesulfonate and 0.2 wt% sodium chloride are added simultaneously and stirred to obtain a composite amine solution decarbonizing agent.
[0088] Decarbonization experiments were conducted using the decarbonization agents from the examples and comparative examples. The CO2 absorption amounts are shown in Table 1.
[0089] Table 1 CO2 Absorption
[0090] .
[0091] The comparative experiments above show that, in this invention, the mass ratio of nano-zirconia to lithium oxide is 1:2~3, and the addition amount is 0.1~0.5 wt%. If excessive amounts of nano-zirconia and lithium oxide are added, their dispersibility and stability may be affected, thereby reducing the selectivity and efficiency of the decarburizing agent.
[0092] The technical solution of this invention involves adding nano-sized zirconium oxide and lithium oxide to an amine solution, giving them specific morphologies and dispersibility, thereby improving the performance and stability of the amine decarbonizing agent. If only one of these nanomaterials is added, the performance and stability of the amine decarbonizing agent may be affected, failing to achieve the advantages and effects described in this invention.
[0093] Compared with traditional amine solutions, the nano-composite amine decarbonizing agent of this invention exhibits better corrosion resistance, anti-foaming properties, antioxidant performance, and higher decarbonization selectivity and absorption efficiency. In industrial decarbonization processes, traditional amine solutions are easily affected by oxidation, decomposition, and corrosion, leading to a decline in decarbonizing agent performance and a shortened service life. However, the nano-composite amine decarbonizing agent of this invention utilizes the synergistic effect and superior performance of nano-sized zirconium oxide and lithium oxide to improve the performance and stability of the amine decarbonizing agent, thereby reducing energy consumption and costs in the decarbonization process, resulting in greater economic efficiency and practicality.
Claims
1. A nano-composite amine liquid decarbonizing agent, characterized in that, It contains the following components: a. Amines; b. Nanoscale zirconium oxide with a particle size between 10 and 50 nm; c. Nanoscale lithium oxide with a particle size between 10 and 50 nm; d. Surfactants; e. Auxiliary additives: sodium chloride, potassium chloride.
2. The nano-composite amine liquid decarbonizing agent according to claim 1, characterized in that... The amines are selected from alkanolamines, etheramines, amides, and cyclic amines; the surfactant is sodium dodecylbenzenesulfonate.
3. The nano-composite amine liquid decarbonizing agent according to claim 1, characterized in that... The mass ratio of nano-sized zirconium oxide to lithium oxide is 1:2~3, and the amount of both added is 0.1~0.5 wt% of the total amount of decarburizing agent.
4. The nano-composite amine liquid decarbonizing agent according to claim 1 or 2, characterized in that... The amount of surfactant added is 0.01~0.05 wt% of the total amount of decarbonizing agent.
5. The nano-composite amine liquid decarbonizing agent according to claim 1, characterized in that... The amount of auxiliary additives added is 0.1~0.5 wt% of the total amount of decarbonizing agent.
6. The nano-composite amine liquid decarbonizing agent according to claim 1, characterized in that... The viscosity of the nano-composite amine liquid decarbonizing agent is 20~100 mPa·s, and its solubility in water is 20~35 wt%.
7. A method for preparing a nano-composite amine liquid decarbonizing agent, characterized in that... Includes the following steps: a. Preparation of nanoscale zirconium oxide and lithium oxide: including the following steps: i. Preparation of sol: Dissolve zirconium acetate and lithium acetate in a solvent to a concentration of 0.1~0.5 mol / L; ii. Gelation: The sol prepared above is heated to 50~80℃ and gelation reaction is carried out under the condition of pH 3~6 for 12~14 hours; iii. Drying and calcination: The gel prepared above is dried at 80~120℃ and then calcined at 500~950℃ for 13-15 hours; iv. Post-processing: The calcined product is subjected to plasma treatment, ultrasonic treatment or heat treatment to obtain nano-sized zirconium oxide and lithium oxide; b. Add the above-mentioned nano-sized zirconium oxide and lithium oxide to the amine solution, control their addition amount and dispersibility, and simultaneously add surfactants and auxiliary additives sodium chloride and potassium chloride, and continue stirring and mixing to obtain a nano-composite amine solution decarbonizing agent.
8. The preparation method according to claim 7, characterized in that... The solvent is one or more combinations of ethanol, n-butanol, isopropanol, isobutanol, methanol, ethylene glycol, propylene glycol, dimethylformamide, ethyl acetate, and benzene.
9. The preparation method according to claim 7, characterized in that... The plasma treatment is one or more combinations of plasma-enhanced chemical vapor deposition, plasma-enhanced arc deposition, or plasma-enhanced thermal atom deposition.
10. The nano-composite amine liquid decarbonizing agent according to claim 1, characterized in that... Dispersion is controlled by mechanical stirring and / or ultrasonic dispersion, wherein the ultrasonic dispersion frequency is in the range of 20~40kHz and the time is 30~60 minutes.
Citation Information
Patent Citations
High-dispersity nano-zirconia particles and method for preparing transparent dispersoid of high-dispersity nano-zirconia particles
CN108529674A
Preparation method and application of nano carbon dioxide trapping agent
CN112791707A